Safety and Prognostic Value of Vasodilator Stress Cardiovascular Magnetic Resonance in Patients With Heart Failure and Reduced Ejection Fraction. (September 2020) - Pezel, Théo; Sanguineti, Francesca; Kinnel, Marine; Landon, Valentin; Bonnet, Guillaume; Garot, Philippe; Hovasse, Thomas; Unterseeh, Thierry; Champagne, Stéphane; Louvard, Yves; Claude Morice, Marie; Garot, Jérôme
Abstract : Background: Patients with heart failure with reduced ejection fraction (HFrEF; heart failure with reduced left ventricular ejection fraction <40%) referred for stress cardiovascular magnetic resonance (CMR) may have a less optimal hemodynamic response to intravenous vasodilator. The aim was to assess the prognostic value of vasodilator stress perfusion CMR in patients with HFrEF. Methods: Between 2008 and 2018, consecutive patients with HFrEF defined by left ventricular ejection fraction <40% prospectively referred for vasodilator stress perfusion CMR were followed for the occurrence of major adverse cardiovascular events (MACE), defined by cardiovascular death or nonfatal myocardial infarction. Univariable and multivariable Cox regressions were performed to determine the prognostic value of inducible ischemia or late gadolinium enhancement by CMR. Results: Of 1053 patients with HFrEF (65±11 years, median [interquartile range] left ventricular ejection fraction 38.7% [37.2–39.0]), 1018 (97%) completed the CMR protocol and 950 (93%) completed the follow-up (median [interquartile range], 5.6 [3.6–7.3] years); 117 experienced a MACE (12.3%). Stress CMR was well tolerated without any adverse events. Patients without ischemia or late gadolinium enhancement experienced a lower annual event rate of MACE (1.8%) than those with both ischemia and late gadolinium enhancement (12.0%; P <0.001). Using Kaplan-Meier analysis, inducible ischemia and late gadolinium enhancement were significantly associated with the occurrence of MACE (hazard ratio, 2.46 [95% CI, 1.69–3.60]; and hazard ratio, 2.92 [95% CI, 1.77–4.83], respectively, both P <0.001). In multivariable Cox regression, inducible ischemia was an independent predictor of a higher incidence of MACE (hazard ratio, 2.26 [95% CI, 1.52–3.35]; P <0.001). Conclusions: Stress CMR is safe and has a good discriminative prognostic value to predict the occurrence of MACE in patients with HFrEF. Abstract : Supplemental Digital Content is available in the text.